Emerging adults' intersecting experiences of food insecurity, unsafe neighbourhoods and discrimination during the coronavirus disease 2019 (COVID-19) outbreak. Issue 3 (23rd February 2021) - Larson, Nicole; Slaughter-Acey, Jaime; Alexander, Tricia; Berge, Jerica; Harnack, Lisa; Neumark-Sztainer, Dianne
Abstract: Objective: To examine how food insecurity is related to emerging adults' food behaviours and experiences of neighbourhood safety and discrimination and to identify resources needed to support their health during the COVID-19 outbreak. Design: Rapid response online survey. Participants completed the six-item US Household Food Security Survey Module, a brief measure of food insufficiency, and measures of food behaviours, neighbourhood safety and discrimination. Open-ended questions were used to assess changes in eating behaviours during COVID-19 and needed resources. Setting: C-EAT (COVID-19 Eating and Activity over Time) study invitations were sent by email and text message to a longitudinal cohort. Participants: A total of 218 emerging adults (mean age = 24·6 (sd 2·0) years, 70·2 % female) completed a survey in April–May 2020 during a stay-at-home order in Minnesota. Results: The past year prevalence of food insecurity was 28·4 %. Among food-insecure respondents, 41·0 % reported both eating less and experiencing hunger due to lack of money in the past month. Food-insecure respondents were less likely than those who were food secure to have fruits/vegetables at home and more likely to have frequent fast-food restaurant meals, feel unsafe in their neighbourhood and experience discrimination during the stay-at-home order. Food-insecure adults reported changes including eating more food prepared at home, eating more take-out restaurant meals and purchasing more energy-dense snacks as a result of events related to COVID-19. Resources most needed to support their health included eligibility for more food assistance and relief funds. Conclusions: Food-insecure emerging adults experience many barriers to maintaining healthful eating patterns during COVID-19.